Peningkatan Komitmen Guru Terhadap Profesi Melalui Pengembangan Budaya Organisasi Dan Kepuasan Kerja - Djuanda, Isep (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
Generally, the aim of this research is to analyze how teachers’ commitment to the profession in Madrasah Tsanawiyah Negeri Jakarta Selatan can be improved through organizational culture and work satisfaction. Hence, this research specifically aims to find out, comprehend, and analyze empirically upon 1) the relation between organizational culture and teachers’ commitment to the profession, 2) the relation between work satisfaction and teachers’ commitment to the profession, and 3) the relation between organizational culture and work satisfaction with teachers’ commitment to the profession.This research is conducted as a quantitative study. The population of this research is the teachers of Madrasah Tsanawiyah Negeri (MTsN) Jakarta Selatan as many as 315 in which 177 of them are taken as the samples. The number of the sample was determined by using proporsional random sampling technique with the Slovin formula at a 5% margin of error.The results of the research show: 1) there is a significant positive relationship between Organizational Culture and Teachers’ Commitment to the Profession, which is indicated by correlation coefficient value ry1 = 0,611 and determinant coefficient value ry12= 0,373; 2) there is a significant positive relationship between Work Satisfaction and Teachers’ Commitment to the Profession, which is indicated by correlation coefficient value ry2 = 0,665., and determinant coefficient value ry22= 0,442; and 3) there is a significant positive relationship between Organizational Culture and Work Satisfaction with Teachers’ Commitment to the Profession, which is indicated by correlation coefficient value ry12 = 0.677., and determinant coefficient value ry122= 0,458.